PENGARUH ARANG TANDAN KOSONG KELAPA SAWIT PADA SIFAT MEKANIK KARET KOPLING KENDARAAN BERMOTOR - Popy Marlina; Tri Susanto (Jurnal Dinamika Penelitian Industri, 2018)
The charcoal of oil palm empty fruit bunches can be used as a filler in the making of rubber clutch of motorcycle vehicles. Oil palm empty fruit bunches is a waste processing of palm oil and renewable resources. This research aimed to determine the effect of TKKS charcoal on the mechanical properties of the rubber clutch of two-wheel motor vehicle. The effect of TKKS charcoal consentrations (15, 25, 35, 45 and 55 phr, respectively) on the abration resistance, flex cracking resistance, oil resistance and density were evaluated. The experimental research used non Factorial Completely Randomized Design and each treatments was replicated three times. The results showed that the best properties fullfilled the requirements of commercial rubber clutch of motorcycle vehicles was using of 35 until 55 phr of TKKS charcoal.  This range showed the mechanical properties of: 397.5  until 432,5 mm3 in abration resistance, 20 until 25 kcs in flex cracking,  13,2 until 14,0% for oil resistance and  1,044 until 1, 112 g/cm3 for density.